Demography, labour market and replacement migration: trends, policies, and prospects in the Portuguese case - Abreu, Alexandre (2009)
This article seeks to contribute to the debate on the issues of the socioeconomic consequences of demographic ageing in Portugal, the available policy responses to this problem, and replacement migration as a partial solution. It begins by presenting and discussing the demographic ageing dynamics currently in place, as well as their potential consequences; it then lists the available instrumental alternatives and their respective advantages, disadvantages, and structural limitations; and, finally, it analyses the recent Portuguese experience in terms of migration dynamics and policies, under the light of the potential contribution of immigration to mitigating the consequences of demographic ageing.